Hand movement speed in advertising elicits gender stereotypes and consumer responses - Malik, Sumit; Sayin, Eda (John Wiley and Sons Inc, 2022)
Merely observing the hand movement speed with an advertised product can affect consumer perception. Five studies show that hand movement speed when observed (e.g.,watching or even reading the description of slow vs. fast hand interaction with a product) elicits distinct associations in the consumer's mind and affects their responses. We suggest that people implicitly associate speedy movements with a more masculine (than feminine) behavior and use hand movement speed as an input to form evaluations of a touched product. Additionally,we demonstrate that consumers elicit higher product preference when their associations from observed hand movement speed match their own social identity. Thus,female (than male) consumers would prefer an advertised product that is depicted with a gentle (instead of speedy) hand movement—as such observed movement makes,both,the product,and the action-performer be perceived as more feminine. We find support for these effects across different product and advertising contexts. Our findings provide novel evidence on the effect of observed and described hand movements as a signal of gender identity and have significant implications for advertising. © 2021 The Authors. Psychology & Marketing published by Wiley Periodicals LLC